THE INFLUENCE OF RETURN ON ASSET , RETURN ON EQUITY, AND DEBT EQUITY RATIO AGAINST ITS POLICIES AMOUNT OF DIVIDENDS TO ON SEVERAL MANUFACTURING COMPANIES WHO TO THAT IT IS LISTED ON A STOCK EXCHANGE 2014-2018 - Lia Delima; Mohammad Wasil; I. G. A Aju Nitya Dharmani (IJESS International Journal of Education and Social Science, 2020)
The purpose of this studyisdetermine This research aims to mengalisa the influence of return on assets roa ), ( return on equity roe ( ), debt to equity ratio ( der ). dividend policy My research retrieve data from a financial statement the company manufactures food and beverage sector that has been registered in indonesia stock exchange a period of 2014-2018.Kind of research that is used in this research is a quantitative research.Data collection techniques digunakaan research is data collection techniques, documentation a measuring instrument for measuring so very company dividend policy in this research which is using the dividend payout ratio ( ). house of representativesFrom this research result can be drawn conclusions that roa, roe, and der what we call a variable free ( x ) significant and positive values of the national parliament or that which we call the dependent variable ( y ).